2015
DOI: 10.17245/jdapm.2015.15.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Korean version of the Dental Fear Survey

Abstract: BackgroundMany people experience varying levels of discomfort when confronted with the prospect of dental treatment. Dental treatment can be a traumatic experience, especially for children and adolescents with dental anxiety. In this age group, dental fear causes a significant problem in dental management and has been related to severe dental caries and dental pain. The Dental Fear Survey ( DFS ) is the most widely used measure of dental fear. This study was undertaken to develop the Korean version of the DFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…e DFS was developed in 1973 by Kleinknecht et al [12], and it has been translated into numerous languages [8,[25][26][27][28]. e Japanese version of the DFS is found to be of high reliability using Cronbach's alpha ranging from 0.94 to 0.96 [8].…”
Section: Dfsmentioning
confidence: 99%
“…e DFS was developed in 1973 by Kleinknecht et al [12], and it has been translated into numerous languages [8,[25][26][27][28]. e Japanese version of the DFS is found to be of high reliability using Cronbach's alpha ranging from 0.94 to 0.96 [8].…”
Section: Dfsmentioning
confidence: 99%
“…DFS was initially established in the English language and authors have revealed good psychometric properties supporting its validity and reliability among adults in the USA [ 4 , 5 ]. Due to the influence of linguistic and cultural differences, DFS was translated and adapted to several languages including Indian [ 6 ], Greek [ 7 ], Japanese [ 4 , 8 , 9 ], Korean [ 10 ], Norwegian [ 11 ], Hungarian [ 12 , 13 ], Brazilian [ 14 , 15 ], Turkish [ 16 ], Chinese [ 17 ], and Malay [ 18 ]. The DFS was also translated and validated in the Arabic language by Alamri et al and its psychometric properties were assessed in a sample of 12–15 year Saudi school students in Riyadh [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between dental pain and dental fear was studied using Japanese DFS scale in 1988 [ 11 ]. The Korean version of the Dental Fear Scale (K-DFS) was translated and evaluated by Kim et al [ 12 13 14 15 ]. According to Shim et al [ 16 ], the dental fear anxiety scale, a tool used to measure dental fear, was used to distinguish dental fear as dental associative fear and dental fear secondary to age and indirect pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%